Optimizing the Productivity of Traditional Textile Artisans through Education and Training for a Sustainable Cultural Industry - Amanda Setiorini; Ari Dina Krestiawan; Mohammad Annas (Science and Technology Research Centre Universitas PGRI Semarang, 2025)
Lasem handmade batik is part of a cultural heritage that has significant economic potential, but the productivity of its artisans is still low due to limited skills and access to innovation. This problem poses a challenge to cultural preservation efforts in line with sustainable development. This study aims to examine the role of education and training in improving the productivity of Lasem handmade batik artisans. The method used is quantitative, with a sample of 100 artisans purposively selected based on work experience and participation in training. Data were collected through questionnaires and relevant documents, and analyzed using SPSS through validity, reliability, normality, t-test, and F-test. The results showed that education and training have a positive and significant influence, both partially and simultaneously, on the productivity of artisans. The findings confirm that improving access to education and training can strengthen the skills, efficiency and production output of Lasem handmade batik artisans. The implications of this research support the achievement of SDG 8 (Decent Work and Economic Growth) by encouraging capacity building of the cultural sector workforce, as well as SDG 12 (Responsible Consumption and Production) through the preservation of environmentally friendly and sustainable batik production processes. This research contributes to the development of sustainability science by underscoring the importance of empowering traditional communities through education and sustainable innovation.